2023
DOI: 10.1101/2023.02.11.23285800
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Psychometric Properties of the NIH Toolbox Cognition and Emotion Batteries Among Children and Adolescents with Congenital Heart Defects

Abstract: Objective: The NIH Toolbox offers brief, computerized measures of cognitive and psychosocial functioning. However, its psychometric properties were established among typically developing children and adolescents. The current study provides the first comprehensive assessment of its psychometric properties among young patients with congenital heart defects (CHD). Study Design: We prospectively recruited 58 patients with CHD and 80 healthy controls between the ages of 6 and 17. Participants completed the NIH Tool… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…While prior studies indicate structural brain network reorganization, our findings suggest that the global functional network remains largely undifferentiated, with predominantly regional differences. Regional, rather than global differences, may explain higher variance observed in CHD patient scores, but still within normal limits on tests of intelligence (Badaly et al, 2022; Wallace et al, 2023)…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…While prior studies indicate structural brain network reorganization, our findings suggest that the global functional network remains largely undifferentiated, with predominantly regional differences. Regional, rather than global differences, may explain higher variance observed in CHD patient scores, but still within normal limits on tests of intelligence (Badaly et al, 2022; Wallace et al, 2023)…”
Section: Discussionmentioning
confidence: 99%
“…Other investigations have similarly identified regional discrepancies in CHD brains while utilizing the NIHTB. The NIHTB has previously found applications in neurocognitive and psychosocial studies within CHD populations (Badaly et al, 2022; Calderon et al, 2019; Cousino et al; Sahel et al, 2023; Siciliano et al, 2021; Wallace et al, 2023). In a recent comprehensive evaluation of the psychometric properties of the NIHTB-CB and NIHTB-EB among children with CHD, researchers concluded that while the NIHTB may have certain limitations, it remains a valuable tool for CHD analysis and has several correlations and insights (Wallace et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As previously described 18 , executive function (EF) outcomes were measured using standardized cognitive tasks from the NIH Toolbox, the Delis-Kaplan Executive Function System (D-KEFS), the WISC-IV as well as parent-completed ratings from the Behavior Rating Inventory of Executive Function (BRIEF-2) (Table 1B). We considered four subdomains of EF: cognitive flexibility, working memory, inhibition, planning and problem-solving.…”
Section: Methodsmentioning
confidence: 99%